Selection strategies in Hevea - Clement-Demange A; Gnagne M; Legnate H; Nicolas D; Rivano F (In: Traitements statistiques des essais de selection, 12-14 September 1994, Montpellier, France p 227-242)
A survey is presented under these headings: aims of selection; history, current situation and prospects of Hevea breeding; biology of Hevea and selection criteria used in the Cote dIvoire; experimental designs used for genetic recombination and selection; genetic resources and improvement of Amazonian germplasm; the Cote dIvoire selection scheme; choice of parents; genetic control of disease- the case of Microcyclus [ulei]; and conclusion.
Source Year: 1996
Keywords: Cote dIvoire; Genetic improvement; Hevea breeding